Ações em gestão do conhecimento para uma instituição pública de ensino superior: um estudo de caso - Empinotti, Paula Carolina (2023)
Public Institutions of Higher Education (PIHEs) are focused on knowledge, which is the main reason for their existence. So that PIHEs can attract and retain human capital, promote social capital, create and use structural capital, share processes and practices, and encourage collaboration, they must implement and institutionalize Knowledge Management (KM). Thus, the self-assessment or diagnosis to ascertain the Maturity Level in Knowledge Management (NMGC), which identifies the strengths and opportunities for improvement, is the first step for the institutionalization of KM. From the diagnosis it is possible to identify enabling and hindering elements for the implementation of KM and, then, establish an action plan appropriate to its reality. Therefore, the goal of this study is to propose a set of actions aimed at KM at the Universidade Federal do Paraná (UFPR), from a diagnosis of its NMGC and the mapping of the enabling and hindering elements of KM in the institution. To achieve this goal, a descriptive and exploratory research was conducted through a case study. The sample, defined intentionally, was composed of 40 professors and administrative technicians from two administrative organs, being one of strategic level, the Pro-Rector Office of Planning, Budget and Finance (PROPLAN) and one of tactical-operational level, the Earth Sciences Sector (SCT). Data collection and analysis was based on the first phase of the diagnosis for the Brazilian Public Administration proposed by Batista (2012). The data collection method was the structured electronic questionnaire and data analysis followed the steps recommended by the same author. In the perception of the PROPLAN’s servers, UFPR is at Level 3 of maturity in KM - "Introduction (Expansion)", while in the perception of the SCT’s servers, it is at Level 2 - "Initiation". The main enablers were related to technology and the main hinderers were related to the ”People” criterion. Most of the enablers at PROPLAN were mapped as hindrances in the SCT, indicating the need for intensive actions directed to KM in the tactical-operational level organs. The data analysis served as a subsidy to elaborate 13 actions for process improvement and for the development of UFPR’s intellectual capital. The actions are to contribute to and foster KM at UFPR.